Prevalence of Accessory Transverse Foramen in the Dried Cervical Vertebrae of Human Population and its’ Clinical Significance: Systematic Review and Meta-Analysis - Tsegaab Adane; Mekbeb Afework (Anatomical Sciences Journal, 2026)
Background: Variations in number, location, size & shape of foramen transversarium affect the anatomical course of the vertebral vessels, which may cause pathological conditions like vertebra-basilar insufficiency. Knowledge of such variations of the presence of accessory transverse foramina in the cervical vertebrae would be useful in planning the cervical spine surgery, and avoiding postoperative complications. Investigations in the magnitude and types of such variation may thus be important for the relevant clinical practices. The aim of this study is to assess the pooled prevalence and clinical importance of accessory transverse foramen among the dried cervical vertebrae of global human population. Methods: This review is carried out in accordance with the protocol of Systematic reviews and Meta-Analyses (PRISMA) guidelines. Condition, context and population framework approach was used. Articles were searched from PubMed, Scopus, EMBASE, CINHAL and Web of Science. Grey literature from Google and Google scholar were hand-searched. In addition to the above databases searches, a hand search of the major anatomical journals was carried out in the reference lists of all the eligible and selected articles for systematic review. Data is clearly summarised and presented in tabular and narrative forms. In addition, meta–analyses was performed on methodologically comparable studies regarding to the study design, primary, and secondary outcomes. Results: Twenty studies with a total of 3848 dried cervical vertebrae of human population were included for this systematic review and meta-analysis. The pooled global prevalence of the accessory transverse cervical foramen was 17.54 % (95% CI: 13.30-21.77). In this study, heterogeneity was found across the studies as revealed by I2 statistic (I2 = 93.6%, p-value < 0.005). The subgroup analysis showed that the prevalence of unilateral accessory transverse cervical foramen was 66.27% (95 % CI: 58.94-73.60),and that of bilateral accessory transverse cervical foramen was found to be 33.73% (95 % CI: 26.40,41.06), anterior accessory transverse cervical foramen was found to be 30.50% (95 % CI: -0.46,61.47), posterior accessory transverse cervical foramen was found to be 62.83% (95 % CI: 22.67,103.00), complete accessory transverse cervical foramen was found to be 63.22% (95 % CI: 56.27,70.17), and that of incomplete accessory transverse cervical foramen of cervical vertebrae was found to be 36.78% (95 % CI: 29.83,43.73). Eggers’ and Beggs’ test revealed the presence of statistically significant publication bias, p > 0.05 which was also supported by the funnel plot. Conclusions and Recommendation: The pooled global level prevalence of accessory transverse cervical foramen was found to be high. Among these, anterior, complete and unilateral accessory transverse cervical foramen was found to be more prevalent than their counterparts. Knowledge of variations in the presence of accessory FT in the cervical vertebrae would be useful in planning the cervical spine surgery, as well as avoiding postoperative complications Awareness of such large variations may thus be interesting for Neurologists, Neurosurgeons and Medical community in general.